2018
DOI: 10.3389/fmicb.2018.00531
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Molecular Approaches for Aspergillus Detection and Azole Resistance Surveillance in Cystic Fibrosis

Abstract: Aspergillus fumigatus triazole resistance is an emerging concern for treating chronically infected/colonized patients. This study sought to evaluate the performance of PCR assays to detect Aspergillus fungi together with azole resistance in sputum samples from cystic fibrosis (CF) patients. In total, 119 sputum samples from 87 CF patients were prospectively processed for Aspergillus detection by means of mycological culture and four qPCR assays, 2 in-hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
4
17
0
1
Order By: Relevance
“…16 This observation is indirectly confirmed by cohorts reporting higher performance of PCR, both in BAL and serum, in those receiving mould active agents. [21][22][23] Also in our study, the rate of qPCR positivity in GM positive BAL samples was higher form patients receiving mould active drugs compared to those not treated. Better specification which portion of BAL fluid should be used might be warranted, since by testing supernatant, DNA still within the organism or phagocytic host cells might not be detected.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…16 This observation is indirectly confirmed by cohorts reporting higher performance of PCR, both in BAL and serum, in those receiving mould active agents. [21][22][23] Also in our study, the rate of qPCR positivity in GM positive BAL samples was higher form patients receiving mould active drugs compared to those not treated. Better specification which portion of BAL fluid should be used might be warranted, since by testing supernatant, DNA still within the organism or phagocytic host cells might not be detected.…”
Section: Discussionsupporting
confidence: 61%
“…Although in case of fungi other than Aspergillus co-infection might be present, it is unlikely based on negative BAL GM. On the contrary, cases of cross-reactivity of the method with strains of A. flavus have already been described in the literature, 23 and such a false positive result might be particularly likely in case of high fungal burden, as demonstrated in our two cases. From the clinical point of view, a qPCR should detect all species of Aspergilllus, since species other than A. fumigatus might be more prevalent, particularity in some geographical zones, for example, A. flavus in Mediterranean.…”
Section: Discussionsupporting
confidence: 46%
“…The sensitivity and specificity of the MycoGENIE were 92.9 and 90.1%, respectively, using respiratory samples (n = 88) and 100 and 84.6%, respectively, with serum samples; this study detected no CYP51A mutants directly from specimen (Dannaoui et al, 2017). Another study compared the AsperGenius R and MycoGENIE assays for the detection of Aspergillus and resistance mutations in sputum specimens from cystic fibrosis patients (Guegan et al, 2018). Neither test detected any CYP51A resistance mutations, and the AsperGenius R had only limited success in amplifying the CYP51A gene targets, likely due to low fungal burden (Guegan et al, 2018).…”
Section: Molecular Methods To Detect Azole Resistance In Aspergillus mentioning
confidence: 80%
“…Another study compared the AsperGenius R and MycoGENIE assays for the detection of Aspergillus and resistance mutations in sputum specimens from cystic fibrosis patients (Guegan et al, 2018). Neither test detected any CYP51A resistance mutations, and the AsperGenius R had only limited success in amplifying the CYP51A gene targets, likely due to low fungal burden (Guegan et al, 2018). While time efficient, these commercial assays are limited by the fact that CYP51A is a single copy gene, and that they detect only azole resistance involving the tandem repeat.…”
Section: Molecular Methods To Detect Azole Resistance In Aspergillus mentioning
confidence: 99%
“…This significant variation in the proportion of resistance, suggested that patients with chronic airway diseases might be at higher risk of colonization and/or infection with azole-resistant A. fumigatus when compared to general or mixed patient cohorts. Similarly, prevalence of azole resistance in clinical A. fumigatus in French patient populations was dependent on underlying clinical conditions; 1.1% in hematological patients, 1.8% in unselected patients ( Alanio et al, 2011 ), and 8% to 12.2% in patients with cystic fibrosis ( Morio et al, 2012 ; Guegan et al, 2018 ). This finding supports the recommendations by van der Linden et al (2016) about the need to determine azole resistance frequency at the hospital level and within different patient groups.…”
Section: Discussionmentioning
confidence: 98%